Left out but not Forgotten: Should Closer Attention be Paid to Coinfection with Herpes Simplex Virus Type 1 and HIV? - Darrell H S Tan; Rupert Kaul; Sharon Walsmley (Canadian Journal of Infectious Diseases and Medical Microbiology)
Herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2) are among the most common coinfections seen in individuals infected with HIV-1. Most research on HSV-HIV coinfection has focused on HSV-2, and in particular, on its impact on HIV transmission. HSV-2 is associated with micro- and macroulcerations in genital mucosal surfaces, increased numbers of HIV target cells in genital mucosal tissue and increases in plasma HIV viral load of up to 0.5 log10 copies/mL, such that HSV-2 infection increases the risk of both HIV acquisition and transmission. Because plasma HIV RNA levels are a major determinant of rates of CD4 cell decline, HSV-2 coinfection may also adversely affect the progression of HIV disease. Anti-HSV medications have in fact been associated with reciprocal decreases in HIV viral load in short-term studies. These findings have led to the development of several clinical trials of HSV-2 suppression as strategies for preventing HIV transmission and slowing the rate of HIV disease progression. HSV-1 coinfection has largely been ignored from this growing body of research, yet there are several reasons that this coinfection remains an important issue for study. First, the seroprevalence of HSV-1 is consistently higher than that of HSV-2 among both HIV-infected and HIV-uninfected populations, underscoring the relevance of HSV-1 coinfection to the majority of HIV-infected persons. Second, pre-existing HSV-1 antibodies in individuals may modulate the course of subsequently acquired HSV-2 infection; the implications of such changes on HSV-HIV coinfection remain unexplored. Third, HSV-1 and HSV-2 are closely related viruses that share 83% genetic homology. Their virological and pathobiological similarities suggest that their implications on HIV pathogenesis may be similar as well. Finally, HSV-1 is becoming increasingly relevant because the incidence of genital HSV-1 has risen. Although genital herpes is traditionally associated with HSV-2, recent studies have shown that the majority of serologically confirmed primary genital herpes in some settings is attributable to HSV-1. Because the genital tract is an important site of biological interaction between HSV and HIV, this epidemiological change may be clinically important.